Building a Harmonious Family: Combining Cultural Heritage and Religious Values in Ambon City - Manuputty, Feky; Afdhal, Afdhal; Makaruku, Nathalia Debby (Westscience Press, 2024)
The issue of high divorce rates in Indonesia has become a serious concern. To address this, efforts are needed to strengthen family relationships. This research aims to describe that the enduring cultural and religious values play a significant role in fostering family harmony. The study focuses on families in Negeri Hukurila, Ambon City, an area renowned for its deep respect for cultural traditions and social ties. For this purpose, the research employs a qualitative research method using in-depth interviews, observations, and document analysis as data collection techniques. The findings indicate that families in Negeri Hukurila play a pivotal role in preserving cultural values and fostering community solidarity. These traditional cultural values serve as a strong foundation for family harmony, such as the concepts of sarikat and badraheng. Sarikat is a cultural concept emphasizing cooperation and mutual assistance among clans within a community to address tasks or issues. Meanwhile, badraheng underscores the importance of solidarity, mutual support, and collaboration among extended family members of a clan to face potential challenges and conflicts. Additionally, religious values and activities also contribute to strengthening family bonds. Programs like pre-marital counseling and religious education have aided in shaping positive attitudes and behaviors within families. For the people of Negeri Hukurila, the noble culture and religion are inseparable. They liken religion and culture to three foundational pillars (tiga batutungku). Therefore, integrating cultural and religious values becomes essential in enhancing family relationships.